2014
DOI: 10.1093/gbe/evu114
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomic Analysis Reveals Multiple Long Terminal Repeats, Lineage-Specific Amplification, and Frequent Interelement Recombination for Cassandra Retrotransposon in Pear (Pyrus bretschneideri Rehd.)

Abstract: Cassandra transposable elements belong to a specific group of terminal-repeat retrotransposons in miniature (TRIM). Although Cassandra TRIM elements have been found in almost all vascular plants, detailed investigations on the nature, abundance, amplification timeframe, and evolution have not been performed in an individual genome. We therefore conducted a comprehensive analysis of Cassandra retrotransposons using the newly sequenced pear genome along with four other Rosaceae species, including apple, peach, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(53 citation statements)
references
References 45 publications
(76 reference statements)
5
48
0
Order By: Relevance
“…In addition to the typical TRIM elements (L 2 I 1 ), some TRIMs arranged tandemly and contained more than three LTRs and two internal regions, hereafter, referred to as tandemly arrayed (TA)-TRIMs. So far, this peculiar structure was reported only for the Cassandra TRIM which LTRs contain sequences similar to cellular 5S rRNA that is also tandemly arranged (Kalendar et al 2008; Yin et al 2014). However, 5S rRNA sequences were not found in other any TRIM families.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…In addition to the typical TRIM elements (L 2 I 1 ), some TRIMs arranged tandemly and contained more than three LTRs and two internal regions, hereafter, referred to as tandemly arrayed (TA)-TRIMs. So far, this peculiar structure was reported only for the Cassandra TRIM which LTRs contain sequences similar to cellular 5S rRNA that is also tandemly arranged (Kalendar et al 2008; Yin et al 2014). However, 5S rRNA sequences were not found in other any TRIM families.…”
Section: Resultsmentioning
confidence: 97%
“…LTR retrotransposons are among the most prevalent elements in plants, but tandemly arrayed LTR retrotransposons have not been reported. The mechanism by which TA-TRIMs were created was likely due to homologous recombination between different elements (Devos et al 2002; Yin et al 2014). The factors that affect the generations of TA-TRIMs are not clear; however, our data indicate that it is not strongly correlated with TA-TRIM size.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, retrotransposon BARE2 of barley parasitizes BARE1 for its Gag (Tanskanen et al 2007). Non-autonomous groups of LTR retrotransposons including the Large Retrotransposon Derivative (LARD) elements (Kalendar et al 2004) and the Terminal-repeat Retrotransposons In Miniature, the TRIMs Witte et al 2001), both of which lack protein-coding capacity, are abundant and structurally conserved in plant genomes (AntoniusKlemola et al 2006;Wu et al 2012;Yin et al 2014) and found also in insects (Zhou and Cahan 2012), so therefore appear to have been successful at replication. The SINEs, which unlike the non-autonomous LTR retrotransposons constitute an order of their own , comprise the diverse sequences that can be propagated by the enzymatic machinery of the LINEs (Goodier and Kazazian 2008;Vassetzky and Kramerov 2013).…”
Section: Non-autonomous Transposable Elements As the Genome "Dark Matmentioning
confidence: 99%